THE POTENTIAL DEVELOPMENT STRATEGY OF PESANTREN LITERATURE TO SUPPORT A RELIGIOUS TOURISM TOWARDS A CREATIVE INDUSTRY - Faridi, Abdurrachman (Language Circle: Journal of Language and Literature, 2011)
Pesantren’s literature is a cultural treasure which exists in Indonesia. Pesantren’s enchantment can be viewed from many sides; i.e. environment, education, teaching, human, even customs and arts. These conditions provide a variety of potential to be optimized. The aim of this study is to expose the potential and model of pesantren’s literature to support religious tourism as a creative industry. The result of this study is to optimize the potential development strategy of pesantren’s literature and to support religious tourism as a creative industry. Pesantren’s literature is used as one of religious tourism attractions that brings the economic life towards a creative industry, and to create other economic activities beneficial for the grassroots’ level. Keywords: pesantren’s literature, religious tourism, creative industry